Independent invention in Italy during the liberal age, 1861-1913 - Alessandro Nuvolari; Michelangelo Vasta (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2013)
In this paper we examine the phenomenon of independent invention in Italy during the liberal age (1861-1913). We make use of a new dataset comprising all patents granted in Italy in five benchmark years: 1864-65, 1881, 1891, 1902 and 1911. We carry out the following exercises. First we examine the relative shares of independent, corporate and foreign inventions and their evolution over time and across industries. Second, by exploiting the peculiarities of Italian patent legislation which established a maximum patent length of fifteen years and a flexible renewal scheme which allowed inventors to maintain a patent 'alive' for almost any specific duration, we assess the relative quality of independent and corporate patents. Our results indicate that in Italy independent inventors provided an important contribution to technological change but the quality of their patents was significantly lower than that of firms and of foreign patentees.
Keywords: N73; O31; 330